Community Empowerment Through Socialization of Making Natural Mosquito Repellent Spray from Lemongrass and Basil Leaves - Suhariyati; Nadila, Erly; Uswatun Khasanah; Muhammad Nur Wijaya Sputra; Hamka Lukmanul Hakin; Mellysa Nur Ramadhan; Nabila Eka Nanda (Society : Jurnal Pengabdian Masyarakat, 2025)
The village of Sumbersari faced an increase in dengue fever cases, while residents still relied on chemical insecticides that were harmful to health and the environment. The lack of knowledge about the use of natural ingredients such as lemongrass and basil prompted the implementation of socialization, education, and practical training for PKK mothers. Activities included providing materials, discussions, pre-tests and post-tests, as well as hands-on practice in making natural sprays. As a result, residents' understanding increased from 75% to 95%, and their independent production skills also improved. This program has successfully empowered the community through safe, environmentally friendly, economical solutions that support healthy lifestyles and sustainable dengue fever prevention.